Clinical Performance as Predictor of Patient Satisfaction with Moderation of Patient Priorities - Adhitya, Kshanti; Untoro, Wisnu (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: Clinical Performance as Predictor of Patient Satisfaction with Moderation of Patient Priorities. This study objective is to determine satisfaction predictors of clinical performance with triage as moderation. This research utilizes cross sectional observation. The research subject was 479 which are the patients, families, patient confidants in the ED of Orthopedic Hospital Soeharso. The hypotheses are tested using regression analysis and moderated regression analysis (MRA) approach. The results depict the satisfaction level up to 42.8% by all predictors of clinical performance. MRA result concluded that the triage variable of the patient can not be moderating variable. Satisfaction predictor, i.e., nursing, physician, and the waiting time, significantly influences the patient satisfaction. Otherwise, Registration factors and advanced/discharge have no influence on satisfaction. Triage as moderating of patient satisfaction is not supported. Keywords: clinical performance, patient satisfaction, emergency priority, triage, Emergency Department.Abstrak: Kinerja Klinis Sebagai Prediktor Kepuasan Pasien dengan Moderasi Prioritas Kegawatan Pasien. Tujuan penelitian ini menguji secara empiris kinerja klinis sebagai prediktor kepuasan pasien dengan moderasi triase. Penelitian ini menggunakan metode observasi cross sectional. Sampel penelitian ini adalah pasien, keluarga, pendamping sejumlah 479. Uji hipotesis dengan model regresi pengaruh langsung dan model pemoderasi dengan Moderated Regression Analysis (MRA). Pengujian hipotesis model pengaruh langsung menunjukkan bahwa tingkat kepuasan yang terjadi dapat dijelaskan 42,8% oleh seluruh prediktor. Hasil analisis MRA menunjukkan semua prediktor, variabel prioritas kegawatan, dan moderat secara bersama-sama berpengaruh terhadap kepuasan. Namun demikian variabel prioritas kegawatan pasien bukan merupakan variabel moderasi. Hipotesis pengaruh langsung prediktor kepuasan yaitu pelayanan perawat, pelayanan dokter, waktu tunggu berpengaruh signifikan terhadap kepuasan pasien didukung. Faktor registrasi dan instruksi pulang/lanjutan tidak berpengaruh terhadap kepuasan. Hipotesis prioritas kegawatan pasien sebagai pemoderasi pengaruh prediktor terhadap kepuasan pasien tidak didukung. Kata kunci: kinerja klinis, kepuasan pasien, prioritas kegawatan, triase, IGD.